Critical analysis of the digital educational resources proposed by the Ministry of Education of Chile in the student textbook for the subjects of Biology and Chemistry in Secondary Education (Educational Knowledge, 2021)
Digital resources are an important tool in the daily lives of all sectors of society, making it essential to understand their quality, especially in the educational field, such as those proposed by the Ministry of Education in textbooks.This qualitative research examines the digital educational resources included in Chilean secondary school Biology and Chemistry textbooks from 2018. The study aimed to determine the availability, pedagogical role, and quality of these resources through content analysis of a sample of three secondary school Biology textbooks (grades 1, 2, and 3-4) and three secondary school Chemistry textbooks (grades 1, 2, and 3-4).The research revealed that 24 out of 76 resources were unavailable in the Biology textbooks, and 67 out of 148 resources were unavailable in the Chemistry textbooks. In the pedagogical role of the resources, the informative aspect predominates over the demonstrative and interactive aspects in both disciplines. Finally, regarding the quality of the resources, defined as excellent, fair, and poor, it is observed that the Chemistry textbooks provide higher quality resources.
Keywords: Digital resources; Biology; Chemistry; education; textbooks